My fair lady - Lerner, Alan Jay, 1918-1986; Loewe, Frederick, 1901-1988; Cukor, George, 1899-1983; Hepburn, Audrey, 1929-1993; Harrison, Rex; Holloway, Stanley; Hyde-White, Wilfrid; Cooper, Gladys, 1888-1971; Brett, Jeremy, 1933-1995; Bikel, Theodore; Shaw, Bernard, 1856-1950 (Warner Home Video, 1998)
A Cockney waif is transformed by a linguistics professor into an elegant lady.